2019
DOI: 10.5741/gems.54.4.418
|View full text |Cite
|
Sign up to set email alerts
|

The Gemological Characteristics of Pipi Pearls Reportedly from Pinctada Maculata

Abstract: I n the Polynesian language, pipi means "small" or "tiny" and is used to refer to the small, predominantly yellow or "golden" pearls that originate from the bivalve mollusk Pinctada maculata (Gould, 1846). As the smallest mollusk species in the Pinctada genus, Pinctada maculata rarely exceeds 5 cm when measured in the anterioposterior or dorsoventral positions. The mollusk lives in the Indo-Pacific Ocean, mostly around French Polynesia and the Cook Islands, where they are often found in association with the Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…This observation is also consistent with the majority of natural pearls tested in all GIA's pearl testing locations. Tight or minimal growth structure is commonly observed in natural pearls produced by many mollusk species of both nacreous and non-nacreous pearls (Krzemnicki et al, 2010;Scarratt et al, 2012;Karampelas, 2017;Nilpetploy et al, 2018b;Scarratt and Hänni, 2004;Wing Yan Ho and Zhou, 2014;Wing Yan Ho, 2015;Wing Yan Ho and Yazawa, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This observation is also consistent with the majority of natural pearls tested in all GIA's pearl testing locations. Tight or minimal growth structure is commonly observed in natural pearls produced by many mollusk species of both nacreous and non-nacreous pearls (Krzemnicki et al, 2010;Scarratt et al, 2012;Karampelas, 2017;Nilpetploy et al, 2018b;Scarratt and Hänni, 2004;Wing Yan Ho and Zhou, 2014;Wing Yan Ho, 2015;Wing Yan Ho and Yazawa, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Irregular dense core structures have only been observed in natural pearls, in the authors' experience, and have not been reported in any NBC pearls. However, an off-round feature associated with the main core in sample 3-5 looks suspicious and could be construed as being a light gray CaCO 3 "seed" feature sometimes found in NBC pearls (Krzemnicki et al, 2010(Krzemnicki et al, , 2011Nilpetploy et al, 2018a;. Thus, if this pearl was tested without any supporting provenance, it could be interpreted as being NBC.…”
Section: Macro Image Rtx Image μ-Ct Imagementioning
confidence: 98%
See 3 more Smart Citations